Arab Women’s Revolution Against Patriarchy In The Cyber Feminist World - Abdul Givari Pratama Amboy; Abdul Basid (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
Cyberfeminism is a phenomenon of feminist groups adapting to developments in technology, information, and communication. This phenomenon of existence is quite attractive in itself, as is how this feminist group struggles to defend their rights, especially their activities in the cyber world. The aims of this research are (1) The Rise of Women in Global Civilization, (2) Critique of Patriarchal Culture, (3) Posthuman Thinking. Posthumanism has begun to be implemented. The research method uses a qualitative type of content analysis whose data comes from five Arab feminist blog sources. This data is collected through documentation techniques and analysed using the Milles & Huberman analysis style. The results show that (1) feminist women experience development in achievements and a consistent environment for society, (2) feminist groups still carry out protests against patriarchal culture, (3) Arab feminist women can adapt to the technological, information, and communication environment in voice their arguments. This research introduces a new perspective on the critique of patriarchy, often associated with anarchic acts, demonstrations, or other threatening behaviors. Through the lens of cyberfeminism, the study highlights that criticism of patriarchal culture can be expressed positively and constructively. Data collected from various news sources illustrate actions that are appreciated by society, such as achievements, independence, and innovative breakthroughs. Consequently, this critique is no longer perceived as a threat but rather as a meaningful effort that drives change and gains broad acceptance.